2018
DOI: 10.1080/14737167.2019.1525294
|View full text |Cite
|
Sign up to set email alerts
|

Adding two culture-specific ‘bolt-on’ dimensions on the Thai version of EQ-5D-5L: an exploratory study in patients with diabetes

Abstract: Preliminary findings suggest that AK, but not IR, may be a useful addition to the EQ-5D questionnaire for use with Thai patients. Further studies in diverse populations are needed to examine the impacts of the proposed new dimensions and determine if these cultural adaptations are justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Of the 28 articles that were included, 3 articles were studies that identified possible bolt-ons (category A "identification or development of possible suitable bolt-ons"), [23][24][25] 13 articles were psychometric performance studies (category B "psychometric performance studies"), 8,26-37 and 6 articles were valuation studies of EQ-5D 1 bolt-on (category C "health state valuation studies"). 19,20,[38][39][40][41][42] Furthermore, 3 articles were categorized as both categories A and B, [43][44][45] and 3 articles as both categories A and C. 13,21,38 Study populations consisted of a healthy population (n = 17 articles: general public, 13,[19][20][21]24,25,27,30,36,38,[40][41][42][43] random households, 44,45 faculty members 39 ) and patients (n = 11 articles: individuals with a chronic condition, 23 visitors of an outpatient eye clinic, 26 cognitive impaired elderly patients, 18 patients with diabetes, 28 general injury patients, 29,31,35 patients listed for cataract surgery, 32,34 stroke patients, …”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 28 articles that were included, 3 articles were studies that identified possible bolt-ons (category A "identification or development of possible suitable bolt-ons"), [23][24][25] 13 articles were psychometric performance studies (category B "psychometric performance studies"), 8,26-37 and 6 articles were valuation studies of EQ-5D 1 bolt-on (category C "health state valuation studies"). 19,20,[38][39][40][41][42] Furthermore, 3 articles were categorized as both categories A and B, [43][44][45] and 3 articles as both categories A and C. 13,21,38 Study populations consisted of a healthy population (n = 17 articles: general public, 13,[19][20][21]24,25,27,30,36,38,[40][41][42][43] random households, 44,45 faculty members 39 ) and patients (n = 11 articles: individuals with a chronic condition, 23 visitors of an outpatient eye clinic, 26 cognitive impaired elderly patients, 18 patients with diabetes, 28 general injury patients, 29,31,35 patients listed for cataract surgery, 32,34 stroke patients, …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Overall, only 1 study scored "doubtful" on the COSMIN Risk of Bias checklist, whereas all other studies scored "inadequate." Considering the quality of studies per subject, 1 study scored "adequate" on PROM development, 38 3 studies scored doubtful, 21,28,42 and 24 studies scored inadequate. Furthermore, content validity was found to be inadequate again in 25 studies and doubtful in the remaining 3 studies.…”
Section: Quality Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations